Association between Helicobacter Pylori Infection and Iron Deficiency Anemia: A Cross Sectional Study - Rahman, Anisur; Raihan, ASMA; Ahmed, Dewan Saifuddin; Karim, Mohammad Enamul; Saeed, Atia; Siddique, Abu Raihan; Sadat, SM Anwar (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Helicobacter pylori (H. pylori) remains one of the most common worldwide human infections and is associated with a number of important upper gastrointestinal (GI) conditions including chronic gastritis, peptic ulcer disease, gastric carcinoma and special type of lymphoma. Anaemia is a common disorder in developing countries and the commonest cause is iron deficiency. There are many causes for high prevalence of this disorder in our society, many are well-known and investigated while some are new and not well established. Although H. pylori associates peptic ulcers and gastric malignancy can cause bleeding, resulting in iron deficiency, but majority of patients infected with H. pylori does not have ulcer or malignancy. They usually have chronic gastritis that is not associated with GI bleeding. About 35% of iron deficiency anaemia cases remain unexplained after a gastrointestinal evaluation. Recently investigation focused on the role of H. pylori, in the development of extra-gastrointestinal diseases including Iron deficiency anaemia. Methodology: This observational, cross sectional study was carried out at BSMMU, Dhaka from July 2010 to October 2011 to find out the association between H. pylori infection and iron deficiency anemia in Bangladeshi adults. Patients with dyspepsia and indication of upper GI endoscopy were initially enrolled in the study and finally a total of 168 subjects were included based on inclusion and exclusion criteria. Result: Among 168 patients, 105 (62.5%) were male and 63(37.5%) were female with the mean age of 33.25 years. On endoscopy, 147(87.5%) of the patients had normal findings and 21(12.5 %) had erosive gastritis. None of them had hemorrhagic erosive gastritis. Among 168 patients, 115(68.45%) were positive and 53(31.55%) were negative for H. pylori by rapid urease test. In our study, we have found a significant low mean serum ferritin level (P<0.001) in H. pylori infected patients. This result is consistent with most of previous data concerning the effect of H. pylori infection on iron metabolism. This study has also revealed a significant (P<0.001) lower value of mean MCV and MCH in H. pylori positive patients. Regarding hemoglobin value, our study has showed no significant (P>0.05) different in hemoglobin level according to H. pylori status. Conclusion: Though there was no significant low hemoglobin level in our study, mean hemoglobin level was low in H. pylori positive patient. In our study H. pylori was not significantly associated with iron deficiency anemia but it was significantly associated with iron deficiency. J Bangladesh Coll Phys Surg 2020; 38(2): 68-78